Hubungan Pendidikan Dengan Kejadian Anemia Pada Ibu Hamil Di Puskesmas Pampang Kota Makassar: Relationship of Education Level with Anemia Events in Pregnant Women in Pampang Makassar City - Hamraa Bachtiar; Nadyah Haruna; Andi Alifiyah Ayu Delima (Jurnal Midwifery, 2023)
Introduction Anemia during pregnancy is referred to as a "potential danger to mother and child" or "anemia is a potential danger to mother and child" so it is something that needs to be considered because it will have an impact on the health of the mother and child. Anemia can be influenced by internal and external factors, and education is one of the external factors that can influence the ability of pregnant women to receive and process health information during pregnancy. The pregnancy phase determines the ability of the child to be born, because development and growth are determined since the fetus is in the womb. Knowing about the incidence of anemia during pregnancy is something that really needs to be considered so that it is not only the responsibility of pregnant women but also the surrounding family who will accompany them throughout pregnancy. Method This study is a quantitative study with a cross sectional design, the sample technique uses purposive sampling with the total sample studied as many as 239 pregnant women and has fulfilled the research criteria. The research data was analyzed using the chi square test. Result This study obtained pregnant women who were anemic as much as 72.4% and the results of bivariate analysis showed that the level of education did not significantly affect the incidence of anemia in pregnant women with a p value of 0.258> 0.000. Conclusion This study shows that the level of education does not affect the incidence of anemia in pregnant women at Puskesmas Pampang Makassar City